Penerapan Diversifikasi Manajemen Kepemimpinan Pendidikan dalam Meningkatkan Efektivitas dan Fungsi Edukatif Koperasi Sekolah - Bunga Citra Lestari; ‘Isyaturrodliyah ‘Isyaturrodliyah; Khoirunisa Rahma Feriska; Siswadi Siswadi (LP3M IAI Al Urwatul Wutsqo Jombang, 2026)
This study aims to analyze the implementation of school cooperative management and management diversification in improving management effectiveness and the educational function of cooperatives. The study employs a qualitative approach using library research based on books, scientific journals, and relevant articles published within the last five years. Data analysis uses an interactive model consisting of data reduction, data display, and conclusion drawing, supported by source triangulation to ensure validity. The findings indicate that school cooperatives have implemented basic management functions; however, their practices remain administrative rather than strategic. Transformational leadership plays a crucial role in enhancing member participation and fostering organizational innovation. Business diversification is proven to improve income stability and strengthen the cooperative’s role as a contextual learning medium through experiential learning. Additionally, the use of digital technology supports efficiency and transparency in cooperative management. This study contributes by integrating leadership, diversification, and contextual learning concepts into school cooperative management. However, its limitation lies in the use of secondary data, which does not fully represent empirical conditions. Future research is recommended to adopt field-based approaches for more comprehensive results